2011
DOI: 10.1007/s10895-011-0962-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photo-Physical Characteristics of ESIPT Inspired 2-Substituted Benzimidazole, Benzoxazole and Benzothiazole Fluorescent Derivatives

Abstract: Novel 2-(1H-benzimidazol-2-yl)-5-(N,N-diethylamino) phenol, 2-(1,3-benzoxazol-2-yl)-5-(N,N-diethylamino) phenol, 2-(1,3-benzothiazol-2-yl)-5-(N,N-diethylamino) phenol and their derivatives have been synthesized from p-N,N-diethyl amino salicylaldehyde with different substituted o-phenylenediamine or o-aminophenol or o-aminothiophenol and their photo-physical properties were studied. Effects of solvent polarity in the absorption-emission properties of synthesized compounds were investigated. All these compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…This is a very fast (picosecond) mechanism, faster than that of the electron transfer, and is dictated by a tautomeric equilibrium that yields the ESIPT product upon excitation. [14][15][16][17][18][19] This effect is responsible for the observed high Stokes shift. Upon excitation of the ion-free probe 6 an electron is transferred from the phenanthroline moiety to the fluorophore and fluorescence is quenched.…”
Section: Resultsmentioning
confidence: 99%
“…This is a very fast (picosecond) mechanism, faster than that of the electron transfer, and is dictated by a tautomeric equilibrium that yields the ESIPT product upon excitation. [14][15][16][17][18][19] This effect is responsible for the observed high Stokes shift. Upon excitation of the ion-free probe 6 an electron is transferred from the phenanthroline moiety to the fluorophore and fluorescence is quenched.…”
Section: Resultsmentioning
confidence: 99%
“…All the measurements were carried out by keeping the parameters constant such as solvent and slit width. Relative quantum yields of synthesized compounds in different solvents were calculated by using formula 1 . The quantum efficiency of compound 8a was found to be more (0.854) as compared with compounds 8b , 8c , 8d ( 8b = 0.473, 8c = 0.480, and 8c = 0.612).…”
Section: Resultsmentioning
confidence: 99%
“…The imidazole unit [14,15] is a newer fluorescent group that is becoming important in the field of chemosensors given its fluorescence off-on behavior that results from its particular structural properties [16]. Park and coworkers [17] have shown that a proper substitution of a tetraphenylimidazole scaffold can lead to white light-emitting compounds by the combination of excited-state intramolecular proton transfer and restricted energy transfer.…”
Section: Introductionmentioning
confidence: 99%